Law and the Regulation of Medicines - Jackson, Emily (Bloomsbury Publishing (UK), 2012)
The principal purpose of this book is to tell the story of a medicine’s journey through the regulatory system in the UK, from defining what counts as a medicine, through clinical trials, licensing, pharmacovigilance, marketing and funding. The question of global access to medicines is addressed because of its political importance, and because it offers a particularly stark illustration of the consequences of classifying medicines as a private rather than a public good. Two further specific challenges to the future of medicine’s regulation are examined separately: first, pharmacogenetics, or the genetic targeting of medicines to subgroups of patients, and second, the possibility of using medicines to enhance well-being or performance, rather than treat disease. Throughout, the emphasis is on the role of regulation in shaping and influencing the operation of the medicines industry, an issue that is of central importance to the promotion of public health and the fair and equitable distribution of healthcare resources.